Sundays at Tiffany's - Patterson, James, 1947-; Charbonnet, Gabrielle (New York : Little, Brown and Company, 2008)
A woman meets her imaginary friend from childhood--and falls in love with him.
Keywords: Imaginary companions -- Fiction; Large type books; Detective and mystery stories